Peculiarities of the Lifestyle and Psychological State of Primary Schoolchildren with Bronchial Asthma - Alexandra M. Timofeeva (Педиатрическая фармакология, 2017)
The need to develop an integrated approach to the treatment of children with bronchial asthma is conditioned by a significant increase in morbidity, emergence of more severe forms of the disease and a lack of radical treatment methods. Along with the development and implementation of modern drug treatment methods, the most topical issues are a consideration of the socio-psychological characteristics of patients and psychological and pedagogical support of children during treatment. Study Objective: To study the lifestyle peculiarities of primary schoolchildren (7–10 years) with bronchial asthma and their psychological state. Patients and Methods. The study included children with bronchial asthma (atopic form, partially controlled course) as well as conditionally healthy peers (health groups I and II) as a comparison group. The psychological status of the observed was assessed using Dembo-Rubinstein self-evaluation method, modified «Human Figure» method, and Varga-Stolin parental relationship test. Results. The study involved 75 children (mean age 8.2 ± 0.6 years, including girls 59%, illness duration 3.2 ± 0.5 years) and their parents (mothers made 79% of them). The comparison group consisted of 54 conditionally healthy children (mean age 8.4 ± 0.3, girls 54%) and their parents (mothers — 85%, fathers — 15%). It is shown that the lifestyle of primary schoolchildren changed due to illness distorts the process of personality development and leads to the emergence of difficulties in the emotional and personality sphere: a reduced background of mood (35; 46.6% versus 11; 20%), blockage of experiences and difficulties in their verbalization (56; 75% versus 25; 46%), defensive-aggressive type of behavior in a stress situation (68; 91% versus 25; 46%), pronounced intrapersonal conflict (47; 62% versus 32; 59%), and communication problems (unsociability, restriction in communication, social fears). Conclusion. Bronchial asthma changes the child's lifestyle, has a negative impact on the psychological state and personality becoming. It is possible to prevent the emergence of negative social consequences of the disease, to smooth out their severity by providing psychological and pedagogical assistance to a child and his family from the time the disease is detected and throughout all treatment stages. The creation and implementation of psychological support programs for families raising children with bronchial asthma at various treatment stages are extremely important and represent a further research direction.